Serotonin signaling is altered in irritable bowel syndrome with diarrhea but not in functional dyspepsia in pediatric age patients - Faure, Christophe; Patey, Natalie; Gauthier, Cindy; Brooks, Elice M; Mawe, Gary M (Gastroenterology (New York, N.Y. 1943), 2010)
In adults, irritable bowel syndrome (IBS) and functional dyspepsia (FD) are chronic conditions that often start during childhood. We investigated mucosal serotonin (5-HT) signaling in children with the idea that data from subjects with a shorter history may improve our understanding of underlying pathophysiological mechanisms. Ninety-eight children undergoing gastroscopy or colonoscopy were studied prospectively. Biopsy specimens were evaluated for inflammation, enterochromaffin cell numbers, 5-HT content, and messenger RNA (mRNA) levels for the synthetic enzyme, tryptophan hydroxylase 1, and the serotonin transporter (SERT) were assessed by quantitative real-time reverse-transcription polymerase chain reaction. Data from 12 children with IBS and 17 with FD were compared with age-matched controls (12 with rectal biopsies and 12 with gastric biopsies) and with subjects with organic disorders. In patients with FD, a small number of immune cells were observed in the gastric mucosa in half of the patients, but no abnormalities with respect to the 5-HT pathway were identified. In patients with IBS, no differences were detected between patients and controls regarding intraepithelial lymphocytes and CD3+ cells in the lamina propria although all patients showed at least a slight inflammatory infiltrate. In the IBS samples, higher 5-HT content (P < .01) and lower SERT mRNA (P < .05) were detected as compared with controls. Severe inflammation in the colonic mucosa had a high impact on 5-HT signaling with a significant decrease in enterochromaffin cells (P < .01) and 5-HT content (P < .01) and a high SERT mRNA expression (P < .01). These results confirm the role of 5-HT signaling in IBS in children and argue against such a role in FD.